2012
DOI: 10.4995/wrs.2012.1080
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the primary cooling rate on the motility and fertility of frozen-thawed rabbit spermatozoa

Abstract: ABSTRACT:In the present study, we examined the effect of primary cooling rates on the motility and fertility of frozen-thawed rabbit spermatozoa. Rabbit semen diluted with an egg-yolk acetamide extender was cooled from room temperature to 5°C at 4 different rates (-0.1, -0.2, -0.4, -0.8°C/min) as a primary cooling step, then semen was frozen in liquid nitrogen vapour. After thawing, sperm cooled at -0.1°C/min showed the highest motility (40.7±7.3%); there were no significant differences between the motilities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…were better than those obtained by other authors (Moc e, Lavara, & Vicente, 2010;Moc e et al, 2014;Viudes-de-Castro et al, 2014) who diluted the semen with freezing extender (containing CPA) at room temperature, that is, without a cooling phase, while results similar to ours were obtained by Moc e, Lavara, and Vicente (2003) and Maeda et al (2012).…”
Section: Moreover Our In Vitro (Motility and Viability) And In Vivo supporting
confidence: 79%
“…were better than those obtained by other authors (Moc e, Lavara, & Vicente, 2010;Moc e et al, 2014;Viudes-de-Castro et al, 2014) who diluted the semen with freezing extender (containing CPA) at room temperature, that is, without a cooling phase, while results similar to ours were obtained by Moc e, Lavara, and Vicente (2003) and Maeda et al (2012).…”
Section: Moreover Our In Vitro (Motility and Viability) And In Vivo supporting
confidence: 79%
“…Although rabbit sperm are considered to be cold shock resistant [3], it is likely that they suffer cold shock damage if cooled too quickly. Previous studies have shown that rabbit sperm cooled at À0.1 to À0.4 C/min resulted in higher in vitro sperm quality than a cooling rate of À0.8 C/min, although these different cooling rates did not result in different rabbit sperm fertilizing capacity [7].…”
Section: Discussionmentioning
confidence: 99%
“…Other recent studies evaluated the effects on how cooling rate [7] or equilibration time [8] affects rabbit sperm quality and fertilizing ability. However, in these studies the cooling, equilibration or both times were a minimum of 55 minutes.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, research has been conducted in the last few years with the objective of optimising the cryopreservation diluents and protocols for rabbit spermatozoa (Iaffaldano et al 2012;Maeda et al 2012;Maya-Soriano et al 2013;Rosato and Iaffaldano 2013) and understanding the parameters that could have an effect on rabbit sperm freezability (Lavara et al 2013). The damage that the spermatozoa accumulate during the cryopreservation protocol causes a decrease in the quality and in in vivo fertilising ability of the spermatozoa.…”
Section: Discussionmentioning
confidence: 99%